2006
DOI: 10.1111/j.1460-9568.2006.04997.x
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular–coerulear interactions: role in hypertension induced by prenatal undernutrition in the rat

Abstract: Rats submitted to fetal growth retardation by in utero malnutrition develop hypertension when adult, showing increased hypothalamic mRNA expression for corticotropin-releasing hormone (CRH) and increased central noradrenergic activity. As hypothalamic CRH serves as an excitatory neurotransmitter within the locus coeruleus (LC) and coerulear norepinephrine plays a similar role within the paraventricular nucleus (PVN) of the hypothalamus, we studied, in both normal and prenatally undernourished 40-day-old anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…This cannot explain the hypertension in the males, however, as they were not fatter than controls. Altered renal sympathetic drive and central sympathetic outflow has previously been implicated in the etiology of the hypertension arising from maternal undernutrition, in the spontaneously hypertensive rat (Perez et al, 2006; Da Silva et al, 2008), high fat feeding rabbits (Armitage et al, 2012) and in our report in offspring of diet induced obese dams which showed increased arterial pressure and sympathoexcitatory activation prior to the onset of obesity (Samuelsson et al, 2010). In a recent study in which we attempted to isolate the consequences of the fat component of the obesogenic diet on offspring arterial pressure the data suggested that maternal obesity rather than fat diet per se is an important determinant of hypertension for both males and females (White et al, 2009; Rudyk et al, 2011).…”
Section: Discussionmentioning
confidence: 52%
“…This cannot explain the hypertension in the males, however, as they were not fatter than controls. Altered renal sympathetic drive and central sympathetic outflow has previously been implicated in the etiology of the hypertension arising from maternal undernutrition, in the spontaneously hypertensive rat (Perez et al, 2006; Da Silva et al, 2008), high fat feeding rabbits (Armitage et al, 2012) and in our report in offspring of diet induced obese dams which showed increased arterial pressure and sympathoexcitatory activation prior to the onset of obesity (Samuelsson et al, 2010). In a recent study in which we attempted to isolate the consequences of the fat component of the obesogenic diet on offspring arterial pressure the data suggested that maternal obesity rather than fat diet per se is an important determinant of hypertension for both males and females (White et al, 2009; Rudyk et al, 2011).…”
Section: Discussionmentioning
confidence: 52%
“…This might indicate the involvement of antipsychotics in more complex hindbrain functional circuits with a role in the efficacy of olanzapine and clozapine in treating negative symptoms and cognitive impairment observed in schizophrenic patients (Dawe et al, 2001). Although Ohashi and co-workers (2000) have indicated the importance of the LC-medial prefrontal cortex functional sequence, i.e., mechanism by which clozapine-like atypical neuroleptics might be more effective for the negative symptoms of schizophrenia, direct PVN-LC functional loop (Perez et al, 2006), allowing a fluent transfer of informations between the PVN-LC complex, can not be excluded from possible actions of neuroleptics. Besides, PVN-dorsal raphe nucleus glutamatergic-serotonergic interactions also play a role in antipsychotics action (Papp et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Exaggerated activity of LC neurons may participate in the allostatic overload of these neurons with potential alteration of the role of the LC as a primary regulator of brain milieu, leading to development of neurodegenerative processes (Mravec et al ., ). Moreover, altered neuronal activity and gene expression of TH in the LC may play a role in the development and maintenance of post‐traumatic stress disorder or hypertension (Perez et al ., ; George et al ., ). However, increased activation of brainstem catecholaminergic cell groups may also promote beneficial consequences.…”
Section: Discussionmentioning
confidence: 98%